THE RE-EMERGENCE OF A SNIFFING CULTURE IN TAMALE-NORTHERN GHANA - Abokyi, S. N.; Akinyoade, A.; Fordjour, F. A. (UDS International Journal of Development, 2024)
Northern Ghana has been associated with the use of hallucinogenic substances and stimulants such as pito, datura, marijuana, kola nuts and tobacco since pre-colonial times. Stimulants such as kola nuts and tobacco featured prominently as essential commodities in long distance trade and very much played a key part in boosting local economies. Aside their socio-economic significance, these stimulants have also been used as alternatives to orthodox medication. Just when sniffing (sundi) was thought to be on the decline, moringa snuff emerged as a stimulant and hallucinogenic substance, seemingly displacing the use of afore-mentioned varieties for recreational and medicinal purposes. Using interviews of users and sellers, personal observation, oral tradition and secondary literature, this paper attempts to provide socio-historical, gender and economic insights into the rise of moringa snuff in northern Ghana. Keywords: Moringa Snuff Addiction, Tamale, Sniffing Culture, Social History